Proglucagon Promoter Cre-Mediated AMPK Deletion in Mice Increases Circulating GLP-1 Levels and Oral Glucose Tolerance. - Sophie R Sayers; Frank Reimann; Fiona M Gribble; Helen Parker; Sagen Zac-Varghese; Stephen R Bloom; Marc Foretz; Benoit Viollet; Guy A Rutter (PLoS ONE)
Background Enteroendocrine L-cells synthesise and release the gut hormone glucagon-like peptide-1 (GLP-1) in response to food transit. Deletion of the tumour suppressor kinase LKB1 from proglucagon-expressing cells leads to the generation of intestinal polyps but no change in circulating GLP-1 levels. Here, we explore the role of the downstream kinase AMP-activated protein kinase (AMPK) in these cells. Method Loss of AMPK from proglucagon-expressing cells was achieved using a preproglucagon promoter-driven Cre (iGluCre) to catalyse recombination of floxed alleles of AMPKα1 and α2. Oral and intraperitoneal glucose tolerance were measured using standard protocols. L-cell mass was measured by immunocytochemistry. Hormone and peptide levels were measured by electrochemical-based luminescence detection or radioimmunoassay. Results Recombination with iGluCre led to efficient deletion of AMPK from intestinal L- and pancreatic alpha-cells. In contrast to mice rendered null for LKB1 using the same strategy, mice deleted for AMPK displayed an increase (WT: 0.05 ± 0.01, KO: 0.09±0.02%, p<0.01) in L-cell mass and elevated plasma fasting (WT: 5.62 ± 0.800 pg/ml, KO: 14.5 ± 1.870, p<0.01) and fed (WT: 15.7 ± 1.48pg/ml, KO: 22.0 ± 6.62, p<0.01) GLP-1 levels. Oral, but not intraperitoneal, glucose tolerance was significantly improved by AMPK deletion, whilst insulin and glucagon levels were unchanged despite an increase in alpha to beta cell ratio (WT: 0.23 ± 0.02, KO: 0.33 ± 0.03, p<0.01). Conclusion AMPK restricts L-cell growth and GLP-1 secretion to suppress glucose tolerance. Targeted inhibition of AMPK in L-cells may thus provide a new therapeutic strategy in some forms of type 2 diabetes.